Glycolysis downregulation is a hallmark of HIV‐1 latency and sensitizes infected cells to oxidative stress. Issue 8 (20th July 2021) - Shytaj, Iart Luca; Procopio, Francesco Andrea; Tarek, Mohammad; Carlon‐Andres, Irene; Tang, Hsin‐Yao; Goldman, Aaron R; Munshi, MohamedHusen; Kumar Pal, Virender; Forcato, Mattia; Sreeram, Sheetal; Leskov, Konstantin; Ye, Fengchun; et al.
Abstract: HIV‐1 infects lymphoid and myeloid cells, which can harbor a latent proviral reservoir responsible for maintaining lifelong infection. Glycolytic metabolism has been identified as a determinant of susceptibility to HIV‐1 infection, but its role in the development and maintenance of HIV‐1 latency has not been elucidated. By combining transcriptomic, proteomic, and metabolomic analyses, we here show that transition to latent HIV‐1 infection downregulates glycolysis, while viral reactivation by conventional stimuli reverts this effect. Decreased glycolytic output in latently infected cells is associated with downregulation of NAD + /NADH. Consequently, infected cells rely on the parallel pentose phosphate pathway and its main product, NADPH, fueling antioxidant pathways maintaining HIV‐1 latency. Of note, blocking NADPH downstream effectors, thioredoxin and glutathione, favors HIV‐1 reactivation from latency in lymphoid and myeloid cellular models. This provides a "shock and kill effect" decreasing proviral DNA in cells from people living with HIV/AIDS. Overall, our data show that downmodulation of glycolysis is a metabolic signature of HIV‐1 latency that can be exploited to target latently infected cells with eradication strategies. SYNOPSIS: The upregulation of glycolysis in activated cells favors HIV‐1 infection and initial viral replication. This study discovers that, to transit into a latent form, which can shield the virus from immunity and antiretroviral drugs, HIV‐1 needs to downregulate glycolysis. Restoration of glycolytic activity is required for HIV‐1 reactivation from latency. Latently infected cells rely on pentose phosphate metabolism and its downstream effectors, i.e., the antioxidant glutathione and thioredoxin pathways, for their survival. Preferential targeting of latently infected cells with drugs inhibiting thioredoxin and glutathione pathways leads to both HIV‐1 reactivation from latency and death of infected cells. Abstract : The upregulation of glycolysis in activated cells favors HIV‐1 infection and initial viral replication. This study discovers that, to transit into a latent form, which can shield the virus from immunity and antiretroviral drugs, HIV‐1 needs to downregulate glycolysis.